Incid??ncia do IPTU sobre bens im??veis p??blicos ocupados por empresas privadas: uma an??lise cr??tica da materialidade constitucional do imposto e suas rela????es com a imunidade tribut??ria rec??proca (Tema 437 da Repercuss??o Geral do STF) - Ganem, Bruna Ribeiro (2015)
This is a critical paper about the incidence of Real State Tax, a municipal tax, in cases where immovable properties and assets held by Federal or States Government are occupied by particular persons, as result of legal use concession contracts or authorized occupation, and its connections with the Mutual Tax Immunity. To achieve these aims, therefore, this study solved the following research problems: in first place, confirmation of the partial unconstitutionality of the National Tax Code in relation to the Constitution of 1946 and its non reception by the current Federal Constitution (1988); construction of the normative matrix rule of the studied tax, since the constitutional level, passing throw the complementary legal settlement, until the local legislation, study that resulted in a doctrinal refinement of the analyzed institute, specially, on its material, personal e quantitative criterions; and, in second place, implications of the Mutual Tax Immunity on the definition of the taxpayer subject, considering the impossibility of transferring the payment responsibility to a non-taxable person, such as the occupant of the public property covered by a concession contract. Furthermore, this research analyzed the Mutual Tax Immunity under the Article 150, VI, ???a???, of the Federal Constitution, in order to identify if it grants a absolute status of protection against the taxation, or if it can be relaxed in cases where the Public Person explore remunerate economic activities. These subjects are under judgment by the Brazilian Supreme Court in the Leading Case number 473 of the general repercussion. Finally, from the theory of the fundamental rights of Robert Alexy, pondering and weighing were developed in order to solve the conflict between the involved constitutional principles: the Free Competition as a key element of an open market economy; and the Mutual Tax Immunity as a guarantor of the Federation Principle.